Failure of pistons engine using finite element analysis - Zarul Shazwan, Zullkafli (2010)
This project deals with analysis the failure of piston engine using FEA. The objective of this thesis is to develop the geometry of piston engine using Solidwork software and to investigate the maximum stress using stress analysis and maximum temperature using thermal analysis. The project describes the finite element analysis techniques to predict the failure of piston and identify the critical locations of the components. Aluminum alloys material was studied in this project which commonly used in industry. The three-dimensional solid modeling of piston engine was developed using the solidwork software. The strategy of validation of finite element model was developed. The finite element analysis was then performed using ALGOR software. The finite element model of the components was analyzed using the static stress with linear material model and steady-state heat transfer. Finally, the maximum stress and maximum temperature were obtained previously are employed as input for the failure of piston. Pistons from petrol engines, from automobiles, will be analyzed. Damages initiated at the top head, ring grooves, pin holes and skirt are assessed. Stresses at the piston crown and pin holes, as well as stresses at the grooves and skirt as a function of land clearances are also presented. The results can also significantly reduce the cost to produce the piston, and improve product reliability and improve the fatigue strength and durability.